Central venous-to-arterial PCO2 difference as a marker to identify fluid responsiveness in septic shock - Boulos Nassar (Nature Portfolio, 2021)
Abstract Defining the hemodynamic response to volume therapy is integral to managing critically ill patients with acute circulatory failure, especially in the absence of cardiac index (CI) measurement. This study aimed at investigating whether changes in central venous-to-arterial CO2 difference (Δ-ΔPCO2) and central venous oxygen saturation (ΔScvO2) induced by volume expansion (VE) are reliable parameters to define fluid responsiveness in sedated and mechanically ventilated septic patients. We prospectively studied 49 critically ill septic patients in whom VE was indicated because of circulatory failure and clinical indices. CI, ΔPCO2, ScvO2, and oxygen consumption (VO2) were measured before and after VE. Responders were defined as patients with a > 10% increase in CI (transpulmonary thermodilution) after VE. We calculated areas under the receiver operating characteristic curves (AUCs) for Δ-ΔPCO2, ΔScvO2, and changes in CI (ΔCI) after VE in the whole population and in the subgroup of patients with an increase in VO2 (ΔVO2) ≤ 10% after VE (oxygen-supply independency). Twenty-five patients were fluid responders. In the whole population, Δ-ΔPCO2 and ΔScvO2 were significantly correlated with ΔCI after VE (r =  − 0.30, p = 0.03 and r = 0.42, p = 0.003, respectively). The AUCs for Δ-ΔPCO2 and ΔScvO2 to define fluid responsiveness (increase in CI > 10% after VE) were 0.76 (p < 0.001) and 0.68 (p = 0.02), respectively. In patients with ΔVO2 ≤ 10% (n = 36) after VE, the correlation between ΔScvO2 and ΔCI was 0.62 (p < 0.001), and between Δ-ΔPCO2 and ΔCI was − 0.47 (p = 0.004). The AUCs for Δ-ΔPCO2 and ΔScvO2 were 0.83 (p < 0.001) and 0.73 (p = 0.006), respectively. In these patients, Δ-ΔPCO2 ≤ -37.5% after VE allowed the categorization between responders and non-responders with a positive predictive value of 100% and a negative predictive value of 60%. In sedated and mechanically ventilated septic patients with no signs of tissue hypoxia (oxygen-supply independency), Δ-ΔPCO2 is a reliable parameter to define fluid responsiveness.